The Structure and Competitiveness of Pakistan’s Basmati Rice Exports - Akmal, Nadeem; Akhtar, Waqar; Shah, Hassnain; Niazi, Muhammad Azam; Saleem, Tariq (Asian Journal of Agriculture and Rural Development, 2014)
This paper provides an analysis on structure of export and competitiveness of Pakistan’s basmati rice over the period 1987-88 to 2011-12 by using revealed comparative advantage (RCA) and regional revealed comparative advantage (RRCA) approaches. Results demonstrate that overall Pakistan’s share in world basmati market has declined from 47% in 1987-92 to 32% in 2008-12 periods at global level and also at regional level i.e. Iran, Saudi Arabia and United Arab Emirates (UAE) markets. However Pakistan has increased its market participation in Oman and United Kingdom (UK) from 60 % to 83 % and 14% to 39 % respectively during the period under analysis. Iran, Saudi Arabia, Sultanate of Oman, UAE, and UK have shown a high geographic concentration in basmati exports from Pakistan however registered a decline in export concentration over time. The analysis of export competitiveness revealed that the Pakistan has revealed comparative advantage in basmati export, implying revealed competitiveness of very high degree as basmati remained a dominant commodity of Pakistan’s export basket. Over the period basmati export competitiveness has shown a fluctuating pattern and clearly diminishing pattern in recent years. This calls for science based strategies to maintain comparative advantage and market participation in basmati rice exports from Pakistan. There is also need to focus on the sector to improve export chain to obtain access in Europeans markets like UK is vital for enhancing future economic performance of rice sector and improving competitiveness in Basmati exports to ensure foreign exchange earnings for country.